Investigation of the Molecular Mechanisms of Antioxidant Damage and Immune Response Downregulation in Liver of Coilia nasus Under Starvation Stress - Wang, Meiyao; Xu, Gangchun; Tang, Yongkai; Su, Shengyan; Wang, Yinping; Zhu, Zhixiang (Frontiers in Endocrinology, 2021)
Commercial fishing of estuarine tapertail anchovy (Coilia nasus), an important anadromous fish species in the Yangtze River of China, has been prohibited due to the serious damage overfishing has caused to the wild population. Research regarding the energy metabolism is important for migratory fish to ensure the continuation of their existence. In this study, we performed, for the first time, a comparative transcriptome analysis of the liver after excessive starvation of C. nasus subjected to long-term starvation stress. The results indicated that the damaging effects involved downregulation of the antioxidant capacity and immune response. The positive response to starvation involved upregulation of the anti-allergy and anticancer capacity, which supports the function of starvation in cancer inhibition, as has also been determined for human beings. This study revealed regulatory pathways, differentially expressed genes (DEGs), and mechanisms leading to damage of the liver in C. nasus affected by starvation. This research contributes information for the further study of the energy metabolism mechanism of C. nasus and provides a theoretical reference for starvation metabolism research of other fish species and even human beings.